Origins and Popularization of Traditional Chinese Therapies in Argentina at the End of 20th Century: the Case of Daniel Alegre - Nicolás Viotti (Chinese Medicine and Culture, 2023)
Various resources of the so-called traditional Chinese medicine, such as taijiquan, massage, diets, or acupuncture, have become widely available in the everyday therapeutic culture of contemporary Argentina. While these resources can be found in the first half of the 20th century, it is evident that from the 1960s onward their presence is more evident, with a strong emphasis from the 1980s on. This article aims to describe the reception and popularization of body and therapeutic techniques of traditional Chinese medicine in Argentina in the 1980s through the case of Daniel Alegre, a key figure in the dissemination of Chinese therapeutic techniques. To do so, it focuses on certain key mediators in the popularization of techniques such as taijiquan and Chinese massage: teachers, promoters, and specialized magazines. All these mediators are key artifacts in the processes of massification and dissemination of traditional Chinese medicine in a broader emerging horizon associated with two simultaneous processes, the Chinese cultural transnationalization and the boom of new forms of holistic management of personal well-being.